Analysis of reintroduction and formation of European bison populations in Belarus (European Bison Conservation Newsletter, 2013)
Reintroductions of European bison to various regions of Belarus were performed in 1994–2000, and in 2005 under the framework of “The program for conservation, distribution and use of European bison in Belarus”. In total 95 European bison – founders of new free-living populations were captured in National Park “Belovezhskaya Pushcha”. Four populations and2 herds were formed up to 2012. The population size of European bison have grown from 347 individuals in 1994 to 1156 individuals (excluding mortality and elimination) in 2012, i.e. by 3.3 times. Created populations have reached various sizes and are at various phases of forming. Aspects of reproduction, population dynamics, mortality and main factors influencing them are given in this publication.
Keywords: European bison reintroduction; conservation program; Belarus